(untitled) (Raparin Journal of Humanities (RJH), 2023)
The principle of legal security is one of the basic principles of public law; Because it is an essential foundation for the existence of the law. Legal security in general is consistent with the principle of legality and one of its basic features. Legal security is concerned with ensuring the stability of the legal rules regulating the affairs of individuals, the clarity of legal rules and the necessity of informing the addressees of them easily and easily, and the state’s commitment not to surprise or surprise individuals with its laws or regulatory decisions that go against their expectations. legitimate. If the general principle established with regard to the effect of the annulment ruling is that it applies retroactively, and all the effects created by the annulment must be erased; This is to give priority to the principle of legality over the principle of legal security. However, the application of the principle of the retroactive effect of the abolition ruling on its release may be problematic for the public interest, and this calls for the necessity of balancing both (the principle of legality and the principle of legal security) in a way that achieves the public interest without compromising the rights of individuals and their legitimate expectations. For this purpose, the comparative administrative judiciary tends to restrict the retroactive effect of the annulment ruling.